Doxycycline Inhibits IL-17-Stimulated MMP-9 Expression by Downregulating ERK1/2 Activation: Implications in Myogenic Differentiation - Hristina Obradović; Jelena Krstić; Tamara Kukolj; Drenka Trivanović; Ivana Okić Đorđević; Slavko Mojsilović; Aleksandra Jauković; Gordana Jovčić; Diana Bugarski; Juan Francisco Santibañez (Mediators of Inflammation)
Interleukin 17 (IL-17) is a cytokine with pleiotropic effects associated with several inflammatory diseases. Although elevated levels of IL-17 have been described in inflammatory myopathies, its role in muscle remodeling and regeneration is still unknown. Excessive extracellular matrix degradation in skeletal muscle is an important pathological consequence of many diseases involving muscle wasting. In this study, the role of IL-17 on the expression of matrix metalloproteinase- (MMP-) 9 in myoblast cells was investigated. The expression of MMP-9 after IL-17 treatment was analyzed in mouse myoblasts C2C12 cell line. The increase in MMP-9 production by IL-17 was concomitant with its capacity to inhibit myogenic differentiation of C2C12 cells. Doxycycline (Doxy) treatment protected the myogenic capacity of myoblasts from IL-17 inhibition and, moreover, increased myotubes hypertrophy. Doxy blocked the capacity of IL-17 to stimulate MMP-9 production by regulating IL-17-induced ERK1/2 MAPK activation. Our results imply that MMP-9 mediates IL-17’s capacity to inhibit myoblast differentiation during inflammatory diseases and indicate that Doxy can modulate myoblast response to inflammatory induction by IL-17.